ETIKA RELIGIUS MASYARAKAT MELAYU: KAJIAN TERHADAP PEMIKIRAN RAJA ALI HAJI - Muhammad Faisal (PERADA, 2019)
This paper aims to describe the religious ethics of Malay society in Raja Ali Haji’s thoughts. In the perspective of Malay society, ethical issues related to the validity of an act inspired the spectrum of Malay thoughts. Since the death of Sultan Mahmud Syah in 1699 from the last dynasty of the Melaka Sultanate, it was marked as the beginning of a radical change in the ethics of Malay society. In this context, the development of Malay ethical thoughts began to critically look for its form. One of Malay thinkers who very concerned about this issue was Raja Ali Haji. He argued that the problem of good and bad of an action was no longer sought in a single frame of feudal leadership, but rather non-structural factors like the existence of syara', religious thoughts or even elements of ethnicity enriching the ethical view in tradition Malay. The approach used in this study was a qualitative approach with Raja Ali Haji's works as primary sources. They included Tuhfatun Nafis, Silsilah Melayu Bugis, Gurindam XII, Muqaddimah fi Intizham, Tsamarat al-Muhimmah, Kitab Pengetahuan Bahasa, Bustanul Katibin. While the secondary sources were the related writing and manuscripts using content analysis. According to Raja Ali Haji, there are four important things in Malay society ethics which must be considered. They are included in the leaders' morality consisting of the principles of justice, deliberation and equality, obedience to Islamic law, language and the establishment of a moral environment.